THE MILITARY GOVERNANCE SYSTEM AND THE MILITARY ART OF THE RULERS IN THE BABURIAN STATE (Conferencea, 2022)
This article provides detailed information on the reforms in the military management system of the rulers during the Baburi dynasty, military positions, titles, military reserves, weapons, martial arts of the rulers during the Baburi dynasty.